Analisis Persepsi Keamanan Nasional India Terhadap Serangan Siber dari Pakistan 2008-2017 - Ratna Ayu Paramitha Pratiwi; Rr. Hermini Susiatiningsih (Journal of International Relations Diponegoro, 2019)
The conflict between India and Pakistan has occurred before independent both of those countries, then continued until they involved in complex pattern of conflict. The development of information and communication technology has influenced on developments leading to cyber conflicts. This conflict makes the perception of India's national security needs to be revised again. In this study, writer discusses Indian cyber security after the Pakistani cyber attack, and looks at India's actions in the cyber attack. This research uses a qualitative method using descriptive. Using Barry Buzan's security theory where individuals and states can be subject and object of reference. The results showed that cyber attacks from Pakistan led to India's critical infrastructure (CI), the existential threats in this case not physical but as cyber. The perception of cyber threats from Pakistan regarded India as confrontation to deal with conflict. Based on this perception has a significant influence of act the of Indian cyber security. Then the writer also looks at Indian national security measures involving nonstate actors involved in cyber conflicts with Pakistan.